2021
DOI: 10.1001/jama.2021.2747
|View full text |Cite
|
Sign up to set email alerts
|

Association of Convalescent Plasma Treatment With Clinical Outcomes in Patients With COVID-19

Abstract: IMPORTANCE Convalescent plasma is a proposed treatment for COVID-19.OBJECTIVE To assess clinical outcomes with convalescent plasma treatment vs placebo or standard of care in peer-reviewed and preprint publications or press releases of randomized clinical trials (RCTs).DATA SOURCES PubMed, the Cochrane COVID-19 trial registry, and the Living Overview of Evidence platform were searched until January 29, 2021. STUDY SELECTIONThe RCTs selected compared any type of convalescent plasma vs placebo or standard of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
225
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(252 citation statements)
references
References 33 publications
10
225
3
2
Order By: Relevance
“…We did not observe any mild or serious transfusion-related adverse events in our patients. This is in agreement with a large cohort of COVID-19 patients receiving CP, where serious complications were rare (<1%) [ 14 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We did not observe any mild or serious transfusion-related adverse events in our patients. This is in agreement with a large cohort of COVID-19 patients receiving CP, where serious complications were rare (<1%) [ 14 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…The latter reached only 50% of its planned enrollment due to the decrease in the number of patients admitted with COVID-19, which could have affected the outcome [ 13 ]. A recent meta-analysis that included 10 RCTs showed no association between CP and all-cause mortality or other clinical outcomes in COVID-19 patients [ 14 ]. Although these trials did not show a consistent improvement in outcome, which is most likely related to the patient population, severity of illness, time of administration, and the plasma antibody titer, they all did show that CP is safe and well-tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperconcentrate preparation of CP appears to be useful, since it can also be administered to individuals who are poor responders to the COVID-19 vaccine and can provide an immediate neutralizing antibody response to those who are in need. Further clinical studies will help clarify the role played by CP in the immunocompromised host with COVID-19 infection and concomitant HM and will elucidate the timing (post-exposure prophylaxis, early use, late use) for its optimal use [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…There are currently many doubts about the efficacy of CCP, especially on the basis of controlled studies [39][40][41], while some clinical experiences have shown a reduction in the mortality of patients with COVID-19 infection [42][43][44][45][46]. These discrepancies may be due to a quantity of bias when designing clinical studies on a disease for which there is still an incomplete knowledge [47].…”
Section: Discussionmentioning
confidence: 99%